The role of social media as a source of academic information for students - Handayani, Fitri; Jalwis; Prahatmaja, Nurmaya (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Social media has a huge impact on students' lives. Social media as a means to view and obtain information. This makes social networking sites very interesting sites and allows for a place to share and also a source of information Purpose: Analyze the role of social media as a means of disseminating academic information for students at the IAIN Kerinci. Method: This research is a type of qualitative research with a case study approach. Data management and data analysis include analyzing and investigating data, grouping data, selecting and classifying what will be processed, searching for and finding patterns. Findings: The impact of social media on users includes building social relationships, increasing interest in economic activities, providing a relaxing effect through entertainment functions, as a means of self-actualization. The role of social media is also very significant for IAIN Kerinci students, apart from being a source of academic information as well as a forum for academic support, learning and as a means of academic communication. Conclusion: The use of social media has become a large source of academic information for IAIN Kerinci students, but it has not yet been utilized significantly for the development of academic quality.